Time Networks: Memory in Network Narrative Films - Tomić, Janica (Array, 2012)
The post 1990s upsurge of “network narrative” or “multi-protagonist films” (which combine several distinct or only tangentially linked stories, all of equal importance, united by common themes as well as the time/space network) is commonly dated back to the release of Robert Altman's film Short Cuts (1993), whose narrative structure is said to have proliferated into “the dominant principle of off-beat storytelling” in contemporary Hollywood and global cinema (Bordwell: Poetics of Cinema 2008). Films like Magnolia (1999), Crash (2004) and hundreds of other recent titles featured in Bordwell's and other listings (Tröhler, Azcona, Steiger, etc.) have also become a subject of substantial scholarly interest: Th. Elsaesser described multi-narrative film as the paradigmatic form of today’s “city film” or the “global city film” (2010). Bearing in mind this ubiquity of the form and its symptomatic readings, as well as the considerable variation among the examples – ranging from romantic comedies like Love Actually (2003) to Michael Haneke’s Code unknown (Code inconnu, 1994) – it is interesting to reflect on the homogeneity when it comes to temporal dimension i.e. the synchronicity of network narrative films. As a rule, these films represent the space through several simultaneous storylines (typically the space of a city, alternatively „New Europe“, or globalized world like in Babel). After illustrating the absence of historical layers in the conventional network narrative, the paper would focus on a few exceptions - Atom Egoyan’s Ararat (2002), Robert Altman’s A Prairie Home Companion (2006) and Roy Andersson’s Songs from the second floor (Sånger från andra våningen, 2000) – to reflect on the modes and effects of opening of the multi-narrative film to cultural memory, trauma or nostalgia.